Advances and emerging challenges in MXenes and their nanocomposites for biosensing applications. Issue 30 (6th July 2022) - Babar, Zaheer Ud Din; Della Ventura, Bartolomeo; Velotta, Raffaele; Iannotti, Vincenzo
Abstract : This review article summarizes the current progress on chemical stability and recent advances/challenges in synthesis of MXenes and their nanocomposites for biosensing applications. Abstract : Two-dimensional materials have unique properties and their better functionality has created new paradigms in the field of sensing. Over the past decade, a new family of 2D materials known as MXenes has emerged as a promising material for numerous applications, including biosensing. Their metallic conductivity, rich surface chemistry, hydrophilicity, good biocompatibility, and high anchoring capacity for biomaterials make them an attractive candidate to detect a variety of analytes. Despite such notable properties, there are certain limitations associated with them. This review aims to present a detailed survey of MXene's synthesis; in particular, their superiority in the field of biosensing as compared to other 2D materials is addressed. Their low oxidative stability is still an open challenge, and recent investigations on MXene's oxidation are summarized. The hexagonal stacking network of MXenes acts as a distinctive matrix to load nanoparticles, and the embedded nanoparticles can bind an excess number of biomolecules ( e.g., antibodies) thereby improving biosensor performance. We will also discuss the synthesis and corresponding performance of MXenes nanocomposites with noble metal nanoparticles and magnetic nanoparticles. Furthermore, Nb and Ti2 C-based MXenes, and Ti3 C2 -MXene sandwich immunoassays are also reviewed in view of their importance. Different aspects and challenges associated with MXenes (from their synthesis to final applications) and the future perspectives described give new directions to fabricate novel biosensors.